Seasonal impacts of microplastic contamination on benthic species using CMPI and PLI indices at Karangsong Estuary, West Java, Indonesia - NOVERITA DIAN TAKARINA; RAHMADYFA MAULIDA AZZAHRAH; LUVIAN WASIS BUDIANTO; NATHAN JOSAFAT SOELIAS; MUHAMMAD ZULFIKAR ANWAR; YANDRA RIZKY SAMUDRA; ATHILA ZAHRA ARIESTA AKHMAD (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Takarina ND, Azzahrah RM, Budianto LW, Soelias NJ, Anwar MZ, Samudra YR, Akhmad AAA. 2026. Seasonal impacts of microplastic contamination on benthic species using CMPI and PLI indices at Karangsong Estuary, West Java, Indonesia. Biodiversitas 27 (1): d270125. https://doi.org/10.13057/biodiv/d270125. Benthic species play a crucial role in estuarine environments. While there is ongoing research on microplastics, information regarding the seasonal variation of microplastics in benthic species remains limited. This study explores the impact of seasonal variation (wet and dry seasons) on microplastic contamination in two representative benthic species at the Karangsong Estuary in West Java, Indonesia. The samples were collected from nine sampling sites in the Karangsong Estuary, with a total of two benthic species and 27 individuals sampled. After a microplastic extraction procedure, Raman Spectroscopy was utilized to identify the microplastic polymers. During the wet season, the predominant types of microplastics found in both Telescopium telescopium and Metaplax longipes are fragments, pellets, and fibers, in that order. The results showed that total microplastic abundance was significantly higher during the wet season than the dry season (χ² = 9.108, p = 0.002), with M. longipes consistently accumulating more microplastics than T. telescopium. During the wet season, microplastic fragments dominated in both species, reaching 0.37 particles g⁻¹ wet mass in T. telescopium (95% CI: 0.06-0.74) and 107.18 particles g⁻¹ wet mass in M. longipes (95% CI: 0-256.00). In contrast, fibers were more prevalent in the dry season, particularly in M. longipes (18.78 particles g⁻¹ wet mass; 95% CI: 6.60-32.80). According to the Comprehensive Microplastics Pollution Index (CMPI), fragments were extremely dominant in M. longipes during the wet season (CMPI = 0.984), while fibers were dominant in T. telescopium during the dry season (CMPI = 0.638). Pollution Load Index (PLI) values for all shapes remained within the low contamination category. Polymer analysis indicated that polyethylene terephthalate (PET) and polyethersulfone (PES) were the dominant polymers in T. telescopium, whereas polypropylene (PP) was most frequently associated with M. longipes. Differences likely influence seasonal variation in microplastic contamination in rainfall, tidal dynamics, surface runoff, and fishing activity between seasons. Although this study is limited by sample size, estuarine coverage, and the use of Raman spectroscopy for polymer identification, the findings highlight clear seasonal patterns in microplastic contamination. These results underscore the importance of season-specific management strategies and support the potential use of M. longipes as a sensitive bioindicator for microplastic pollution in tropical estuaries.